Catalyst free silica templated porous carbon nanoparticles from bio-waste materials - Anuj, Kumar; Gurumurthy, Hegde; Shoriya Aruni, bt Abdul Manaf; Zainab, Ngaini; K. V., Sharma (Royal Society of Chemistry, 2014)
Porous Carbon Nanoparticles (PCNs) with well-developed microporosity were obtained from bio-waste oil palm leaves (OPL) using single step pyrolysis in nitrogen atmosphere at 500–600 8C in tubefurnace without any catalysis support. The key approach was using silica (SiO2) bodies of OPL as a template in the synthesis of microporous carbon nanoparticles with very small particle sizes of 35–85 nm and pore sizes between 1.9–2 nm.